HUBUNGAN ANTARA KADAR LEPTIN DAN ADIPONEKTIN PLASMA PADA PASIEN DENGAN DIALISIS RUTIN - Raka Widiana, I Gde; Kandarini, Yenny; Suwitra, Ketut (journal of internal medicine; Vol. 9, No. 2 Mei 2008, 2012)
Leptin and adiponectin (ADPN) are adipokines with respective pro-atherogenic and anti atherogenic properties. In nonrenal patients, both hyperleptinemia and hypoadiponectinemia are associated with cardiovascular complication. Relationships between serum leptin and ADPN in patients with dialysis is not consistently reported. Objective of this study is evaluate relationships between serum ADPN and leptin in patients with dialysis. A cross sectional study was performed in and 54 HD and 22 CAPD patients. Seventy six patients were enrolled this study, M/F 41/76, aged 48.4±11.4 year, BMI 21.4±2.7 kg/m2, haemoglobin (Hb) 7.9±1.5 mg/dL, blood sugar 94.8±33.5 mg/dL, albumin 4.1±0.4 g/dL, total-cholesterol 177.9±46.3 mg/dL, triglyserida 164.4±104.8 mg/dL, SC 14.3±3.8 mg/dL, TNF 14.40±7.43 pg/mL, ADPN 17.6±7.6 µg/mL, leptin 13068±23589 µg/mL (log leptin 3.7±0.59 µg/ml). Using Spearmans rho analysis there were negative correlation between log-leptin and ADPN (r= -0.39, p= 0.00), and positive correlation between log leptin and Hb (r= 0.25, p= 0.04), insulin(r= 0.44, p = 0.00), total-cholesterol (r= 0.34, p = 0.003), triglyserida (r= 0.41, p= 0.00), and BMI (r= 0.41, p= 0.00), but there was no correlation between log-leptin and albumin, blood sugar, SC and TNF alfa. Using multiple regression to analyze relationship between ADPN and leptin, insulin, Hb, and dialysis modality, we found log leptin independently correlated with ADPN (B= -0.402, p= 0.01, 95%CI B: -1.24 to -0.32). Using multiple regression to analized relationship between ADPN with log-leptin, BMI, total cholesterol, and triglyserida, we found log leptin (beta= -0.3, p= 0.01, 95%CI B: -0.98 to -0.13) and triglyserida independently correlated with ADPN (beta= -0.5, p= 0.00, 95%CI B: -0.008 to -0.003). Serum leptin and triglyseride relate with ADPN. Some metabolic parameters such as insulin resistance, anemia, dialysis modality, nutritional status (BMI and total cholesterol) have indirect relationship with ADPN may be through leptin secretion.
Keywords: leptin, adiponectin, dialysis